(untitled) - Durant, Will (New York, 1935)
In the year 335 the Emperor Constantine, feeling the nearness of death, called his sons and nephews to his side, and divided among them, with the folly of fondness, the government of the immense Empire that he had won. To his eldest son, Constantine II, he assigned the West--Britain, Gaul, and Spain; to his son Constantius, the East--Asia Minor, Syria, and Egypt; to his youngest son, Constans, North Africa, Italy, Illyricum, and Thrace, including the new and old capitals--Constantinople and Rome; and to two nephews Armenia, Macedonia, and Greece. The first Christian Emperor had spent his life, and many another, in restoring the monarchy, and unifying the faith, of the Roman Empire; his death (337) risked all. He had a hard choice: his rule had not acquired the sanctity of time, and could not ensure the peaceable succession of a sole heir; divided government seemed a lesser evil than civil war.
Keywords: Civilization,Văn minh; History,Lịch sử